2014
DOI: 10.1152/ajpendo.00553.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of embryo number and maternal undernutrition around the time of conception on insulin signaling and gluconeogenic factors and microRNAs in the liver of fetal sheep

Abstract: -This study aimed to determine whether exposure of the oocyte and/or embryo to maternal undernutrition results in the later programming of insulin action in the liver and factors regulating gluconeogenesis. To do this, we collect livers from singleton and twin fetal sheep that were exposed to periconceptional (PCUN; Ϫ60 to 7 days) or preimplantation (PIUN; 0 -7 days) undernutrition at 136 -138 days of gestation (term ϭ 150 days). The mRNA and protein abundance of insulin signaling and gluconeogenic factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 60 publications
(60 reference statements)
3
35
0
Order By: Relevance
“…This increase was shown to be due to an enhanced activity of PEPCK which results from decreased methylation of the gene's promoter [13]. Formerly, it was assumed that substantial gluconeogenesis only starts to occur` at birth [22], but more recent publications, using mammalian animal models of intrauterine growth restriction and inadequate maternal nutrition, point towards intra-uterine initiation of gluconeogenesis [13,23,24]. In fetal baboons it was shown that the PEPCK protein, a key enzyme in gluconeogenesis, was upregulated in MNR fetuses [13].…”
Section: 9gmentioning
confidence: 99%
“…This increase was shown to be due to an enhanced activity of PEPCK which results from decreased methylation of the gene's promoter [13]. Formerly, it was assumed that substantial gluconeogenesis only starts to occur` at birth [22], but more recent publications, using mammalian animal models of intrauterine growth restriction and inadequate maternal nutrition, point towards intra-uterine initiation of gluconeogenesis [13,23,24]. In fetal baboons it was shown that the PEPCK protein, a key enzyme in gluconeogenesis, was upregulated in MNR fetuses [13].…”
Section: 9gmentioning
confidence: 99%
“…We have also reported recently that in singleton fetal sheep exposed to maternal undernutrition during either the periconceptional or preimplantation period, there was lower abundance of key insulin-signaling molecules in the liver compared with control fetuses. In contrast, protein abundance of the key insulin-signaling molecules was higher in the liver of twin fetal sheep exposed to periconceptional or preimplantation undernutrition compared with controls (26).…”
mentioning
confidence: 69%
“…All procedures were approved by the University of Adelaide Animal Ethics Committee and by the Primary Industries and Resources South Australia Animal Ethics Committee (26,49).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations